The impact of economic growth on unemployment in Syria during the period (2000-2021) - Kshwar, Loreen Bayan (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to know the impact of economic growth on unemployment in Syria during the period (2000-2021). To achieve this goal, the study used the Angel granger cointegration test, and reached the following results: There is a cointegration relationship between economic growth and unemployment over the period (2000-2021).- - A decline in the economic growth rate will lead to an increase in unemployment rates in the short term. - Every 1% increase in the economic growth rate will lead to a reduction in the unemployment rate by approximately 2% in the long term. Based on the results reached, the researcher recommended the necessity of increasing the competitiveness of the economy and improving the conditions of the labor market in Syria, which would contribute to reducing unemployment rates, creating sustainable job opportunities that are compatible with the workforce, and increasing participation rates in the labor force, which would increase the gross domestic product. This, in turn, stimulates economic growth, focuses on labor-intensive productive projects, and encourages small and medium enterprises to reduce the unemployment problem.